Harnessing Remittances for Productive Use in Nepal - Pant, Bhubanesh (NRB Economic Review, 2011)
Remittances contribute largely to the national economy. The remittances sent home by the migrants affect development at both the household and national levels. At the household level, remittances help to reduce poverty, improve standard of living and attain higher educational levels. At the macro level, remittances could be used for entrepreneurship and productive investment which in turn increases job opportunities and income of the people. At the same time, remittance inflows help to augment foreign exchange reserves and improve the current account position. This paper suggests that workable policies and programs need to be developed by Nepal's policy makers for encouraging the utilization of remittances for productive use in order to promote longer-term growth.